A new approach for the prediction of fatigue life in rolling bearings based on damage accumulation theory considering residual stresses - Hwang, Jae-Il; Poll, Gerhard (Frontiers in Manufacturing Technology, 2022)
Today, the service life calculation of rolling bearings is standardized in ISO 281, based on the theory of Lundberg and Palmgren. In the standard calculation method, material properties such as fatigue limit stress were taken into account by introducing the fatigue limit stress proposed by Ioannides and Harris. This standard calculation method provides a reasonable range of fatigue life in good agreement with experimental results under ideal test conditions such as constant external load. However, complex operating conditions of bearings such as varying loads and oscillating motion are not considered. Therefore, there is a need for a new analytical calculation model that can predict the fatigue life of rolling bearings operating under these complex conditions. This makes it possible to advance the application of rolling bearings and optimize their use in machines such as wind turbines. In the proposed approach, the fatigue life is determined based on the Palmgren-Miner linear damage rule, evaluating the subsurface stresses below the rolling contact using the S-N curve according to the fatigue criterion proposed by Lundberg and Palmgren. All rolling contacts that occur in an internal stress cycle due to the internal dynamic behavior during rotating operations are evaluated individually and referred to as partial damage risks. The partial damage risks are accumulated linearly according to the Palmgren-Miner theory to obtain the load cycle to failure. At this time, the loaded volume is assessed along the depth from the contact area to the core of the bearing ring, which makes it possible to indicate the depth position of fatigue occurrence in terms of crack initiation. The material properties such as the fatigue limit stress and the probability of failure are taken from the S-N curve itself. To consider the residual stress, a simple link concept is suggested by using the ratio of the maximum contact pressure to the yield criteria. The proposed approach can be extended to calculate oscillating fatigue life regarding the number of rolling contacts at a given oscillation amplitude. In this study, it can be confirmed that the analytically determined fatigue lifetime according to ISO 281 is still close to the bearing life test result. In addition, it shows that the results obtained using the proposed approach agree well with the calculation results obtained using ISO 281.